Pengaruh Waktu Pemeraman Terhadap Uji Kuat Tekan Paving Blok Menggunakan Campuran Tanah dan Kapur dengan Alat Pemadatan Modifikasi - Helmahera, Martha; Setyanto, Setyanto; Adha, Idharmahadi (Universitas Lampung, 2016)
Paving block is smaller segments made of concrete with rectangular or square shape many ofwhich have good compressive strength properties, has good compressive strength properties, canwithstand the load in some extent, and easy installation work. Paving blocks made from a mixtureof portland cement or a kind of adhesive hydrolysis, water, and aggregates with or without otheringredients. In this study the process of manufacture of paving blocks will use a mix of soil andlimestone. Moreover, curing of the paving blocks that are expected to increase the strength ofpaving blocks is according to SNI 03-0691-1996. Soil samples tested were from Kota Baru, SouthLampung. The composition of the soil mix and chalk with a variety of curing time 7 days, 14 days,21 days and 28 days as well as to the treatment of pre-combustion and post-combustion of thesample of paving blocks. Based on the results of physical testing the original soil, USCS classifysoil samples as fine-grained soil and belong to the group ML. Results from this study is themanufacture of paving blocks using silt soil and chalk soil material that does not meet thespecifications of SNI 03-0691-1996. For the compressive strength of paving blocks pre-combustion and post-combustion are best shown in curing time of 28 days. The compressivestrength that generated as a whole still does not meet the specifications of the paving block SKSNI 03-0691-1996 that is a minimum compressive strength at 85 kg / cm 2 . As well as the waterabsorption the test value not meet the specifications of the paving block SK SNI - 03 - 0691- 1996is around 3% - 10%.Keywords: Paving blocks, silt soil, compressive strength, soil combustion